Sedimentological and ichnological signatures from a fluvial-dominated delta in subsurface: lajas formation, Middle Jurassic, Neuquén basin, Argentina - Arregui, Mariano Germán (2022)
Transitional marine systems are affected by the interaction of wave, tidal and fluvialprocesses, with different impacts on salinity, turbidity, energy and depositionalrate. Benthic organisms are influenced by these processes, and so, the ichnologicalsignatures of these deposits represent key elements for environmental analysis.The Lajas Formation (Middle Jurassic, Neuquén Basin Argentina) is characterizedby deposits accumulated in shallow transitional marine environments, mainlydeltaic systems. A detailed study of sedimentological and ichnological features ofthe Lajas Formation developed on subsurface core samples allows to reconstructthe depositional conditions and evolution of unit and determine that the prevalentprocesses on the reworking of the sediments is fluvial, with subordinated waveprocesses. Fourteen sedimentary facies were defined, grouped into five faciesassociations: interdistributary plain, distributary channels, fairweather and stormgeneratedwaves bars, delta front mouth bars, and prodelta. The ichnologicalanalysis allows to differentiate 21 trace fossils: representing 5 ichnofacies: Skolithos(Mararonichnus suite), Skolithos (or Rosellia), impoverished Cruziana, Cruziana,Scoyenia and Zoophycos. Two surfaces with Glossifungites suites were recognized,and they are interpreted in two different ways, one related to authigenic changes andthe other as a surface of stratigraphic importance, related to the variation in sea level.Finally, the whole section studied constitutes a prograding fluvio-dominated deltaicsystem, representing a Highstand System Tract, with minor transgressive events.